Defining the human C2H2 zinc finger degrome targeted by thalidomide analogs through CRBN - Sievers, Quinlan L.; Petzold, Georg; Bunker, Richard D.; Renneville, Aline; Słabicki, Mikołaj; Liddicoat, Brian J.; Abdulrahman, Wassim; Mikkelsen, Tarjei; Ebert, Benjamin L.; Thomä, Nicolas H. (Science, 2018)
Thalidomide-targeted degradation - Thalidomide and its analogs improve the survival of patients with multiple myeloma and other blood cancers. Previous work showed that the drugs bind to the E3 ubiquitin ligase Cereblon, which then targets for degradation two specific zinc finger (ZF) transcription factors with a role in cancer development. Sievers et al. found that more ZF proteins than anticipated are destabilized by thalidomide analogs. A proof-of-concept experiment revealed that chemical modifications of thalidomide can lead to selective degradation of specific ZF proteins. The detailed information provided by structural, biochemical, and computational analyses could guide the development of drugs that target ZF transcription factors implicated in human disease. - Science, this issue p. eaat0572 - Structured Abstract - INTRODUCTIONThalidomide, lenalidomide, and pomalidomide are clinically approved therapies for the treatment of multiple myeloma and other hematologic malignancies. These drugs induce rapid ubiquitination and proteasomal degradation of two transcription factors, Ikaros (IKZF1) and Aiolos (IKZF3), by recruiting them to the CRL4CRBN E3 ubiquitin ligase through a Cys2-His2 (C2H2) zinc finger (ZF) domain that is present in both proteins and required for their destruction. - RATIONALETranscription factors have been challenging drug targets because they lack discrete catalytic domains amenable to small-molecule inhibition. Thalidomide analog-induced degradation of IKZF1 and IKZF3 through a C2H2 ZF domain raised the possibility that the >800 C2H2 ZF-containing proteins encoded by the human genome, many of which are putative transcription factors, could be similarly destabilized. We therefore set out to (i) define the human ZF “degrome” in the context of thalidomide, lenalidomide, and pomalidomide; (ii) characterize the ZF-drug-CRBN interaction structurally and functionally; and (iii) determine whether different thalidomide analogs degrade distinct ZFs. - RESULTSUsing a reporter of substrate degradation, we screened 6572 C2H2 ZFs for degradation in the presence of thalidomide, lenalidomide, and pomalidomide, identifying 11 ZF degrons, motifs that are capable of mediating drug-dependent degradation, of which six were found to mediate degradation of their full-length protein. Surprisingly, the 11 ZF degrons lack an identifiable consensus sequence. Saturation mutagenesis of the IKZF1/3 ZF degron and crystal structures of two ZF degrons bound to pomalidomide-engaged CRBN demonstrate that the drug-CRBN interface accommodates ZF degrons with diverse amino acid sequences. Computational docking in combination with in vitro binding assays revealed that a large number of ZFs are capable of weakly binding the drug-CRBN interface, indicating that this interface may be more permissive than suggested by the 11 ZF degrons identified in the degradation screen. To test this hypothesis, we screened the ZF library against two thalidomide analogs with chemical alterations at the ZF-drug-CRBN interface. The two thalidomide analogs induced degradation of distinct sets of C2H2 ZF degrons, including ZFs that bind the CRBN-pomalidomide complex weakly in vitro, but were not degraded by pomalidomide in cells. - CONCLUSIONWe found that thalidomide analogs mediate CRL4CRBN-dependent degradation of a larger number of C2H2 ZF proteins than previously anticipated. ZFs compatible with the drug-CRBN interface show little sequence conservation apart from residues that stabilize the ternary ZF fold. In addition to the complex ZF-CRBN side chain interactions, direct contacts between thalidomide analogs and varying ZF residues provide another layer of specificity. Thalidomide analogs with altered chemical scaffolds thus allow selective degradation of distinct ZF targets. Our results provide a structural and functional basis for the chemical modulation of CRL4CRBN to degrade C2H2 ZF transcription factors. Degradation of C2H2 ZF-containing proteins through derivatized thalidomide analogs may be a general paradigm for therapeutically targeting C2H2 ZF transcription factors, a class of proteins previously perceived to be “undruggable.” Download high-res image Open in new tab Download Powerpoint Thalidomide analogs mediate CRL4CRBN-dependent ubiquitination and degradation of C2H2 ZFs.We created a cellular library in which each cell expresses one of 6572 individual C2H2 ZF domains from the human proteome fused to enhanced green fluorescent protein (eGFP). Cells expressing a C2H2 ZF reporter that is susceptible to thalidomide analog-induced degradation lose their eGFP signal, allowing their identification through a combination of fluorescence-activated cell sorting (FACS) and high-throughput sequencing. Structural and functional studies revealed how the drug-CRBN complex accommodates ZFs with diverse amino acid sequences. On the basis of these results, we tested thalidomide analogs with chemical modifications at the drug-ZF interface and found that these derivatives can degrade different sets of C2H2 ZFs. Our results suggest that chemical modulation of CRL4CRBN may be a more generalizable paradigm to inactivate C2H2 ZF-containing proteins, the largest group of putative transcription factors in the human genome. IRES, internal ribosomal entry site; DMSO, dimethyl sulfoxide. - The small molecules thalidomide, lenalidomide, and pomalidomide induce the ubiquitination and proteasomal degradation of the transcription factors Ikaros (IKZF1) and Aiolos (IKZF3) by recruiting a Cys2-His2 (C2H2) zinc finger domain to Cereblon (CRBN), the substrate receptor of the CRL4CRBN E3 ubiquitin ligase. We screened the human C2H2 zinc finger proteome for degradation in the presence of thalidomide analogs, identifying 11 zinc finger degrons. Structural and functional characterization of the C2H2 zinc finger degrons demonstrates how diverse zinc finger domains bind the permissive drug-CRBN interface. Computational zinc finger docking and biochemical analysis predict that more than 150 zinc fingers bind the drug-CRBN complex in vitro, and we show that selective zinc finger degradation can be achieved through compound modifications. Our results provide a rationale for therapeutically targeting transcription factors that were previously considered undruggable. - A detailed analysis of zinc finger protein degradation by thalidomide may help efforts to “drug” transcription factors. - A detailed analysis of zinc finger protein degradation by thalidomide may help efforts to “drug” transcription factors.
Gesehen am 16.10.2019